Safety and effectiveness of SOFIA/SOFIA PLUS for direct aspiration as first line treatment in patients with acute anterior ischemic stroke: results from the prospective, multicentric SESAME study - Neuberger, Ulf; Marnat, Gaultier; Barreau, Xavier; Pitrone, Antonio; Caragliano, Antonio A.; Killer-Oberpfalzer, Monika; Pfaff, Johannes A. R.; Maurer, Christoph J.; Berlis, Ansgar; Bokkers, Reinoud; Uyttenboogaart, Maarten; Sourour, Nader; et al. (Frontiers in Neurology, 2024)
Background Mechanical thrombectomy is a cornerstone treatment for acute ischemic stroke (AIS) with large vessel occlusion (LVO), yet the optimal technique remains debated. The SOFIA/SOFIA PLUS catheter has emerged as a promising tool for direct aspiration thrombectomy. Purpose This prospective multi-center study, adhering Good-Clinical-Practice guidelines, aimed to evaluate the safety and efficacy of the SOFIA/SOFIA PLUS catheter for direct aspiration as a first-line treatment technique in patients with acute anterior circulation LVO. Materials and methods Between 10/2017 and 12/2021, 246 consecutive patients presenting with AIS due to anterior circulation LVO were enrolled from 14 European centers. Primary treatment with SOFIA catheters was performed within 6 h of symptom onset. Clinical and radiological data were collected, and statistical analyses were conducted. Results The mean age of the included patients was 71.6 ± 13.9 years, with 44.7% being male. Primary aspiration achieved complete recanalization in 72.8% of patients, with functional independence observed in 63.8% after 90 days. Secondary outcomes included a median NIHSS of 4 at 24 h post-procedure, median ASPECTS of 7 on follow-up imaging, and a mortality rate of 24.4% at 90 days. No device malfunctions were observed, and the rate of symptomatic intracranial hemorrhage was 4.4%. Conclusion Primary aspiration with the SOFIA/SOFIA PLUS catheter demonstrates favorable safety and efficacy profiles in the treatment of anterior circulation LVO. These findings support the utilization of this technique as a first-line approach in mechanical thrombectomy for AIS, contributing to the growing body of evidence endorsing the effectiveness of direct aspiration thrombectomy in stroke management.